STUDY ON THE EFFECT OF POLYETHYLENE TEREPHTHALATE COMPRESSIVE STRENGTH OF CONCRETE - Umi Latifah; Syafwandi (Neutron, 2020)
Plastic waste is the largest contributor in the world and belongs to the class of materials that can not be broken down by organisms (non-bio-degradable) and durable (persistent) which does not rot. It can be seen directly from this waste that is lightweight and not easily deformed. Terephthalate polyethylene plastic types are widely used as mineral water bottles can be recycled as coarse aggregate for lightweight concrete manufacture. In this study, carried out the loading test compressive strength. To determine the properties of lightweight concrete, tested the modulus of elasticity, compressive strength, and strong Pull. The physical and mechanical nature of light concrete in the use of waste plastics PET instead of coarse aggregate must be following existing regulations. The compressive strength of concrete with the highest in the age of 28 daycare that is equal to 23.973 MPa. The highest tensile strength value contained in the concrete to the age of 28-day care is equal to 2,782Mpa.